2022
DOI: 10.1002/hep4.1906
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Omega‐3 Polyunsaturated Fatty Acids on Lipid Metabolism in Patients With Metabolic Syndrome and NAFLD

Abstract: Nonalcoholic fatty liver disease (NAFLD) is the most common chronic liver disease. n‐3 polyunsaturated fatty acids (n‐3‐PUFAs) have been reported to ameliorate the progression of NAFLD in experimental studies; however, clinical trials have yielded contradictory results. The aim of our study was to assess the effects of n‐3‐PUFA administration on lipid metabolism and the progression of NAFLD in patients with metabolic syndrome. Sixty patients with metabolic syndrome and NAFLD were randomized in a double‐blind p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 45 publications
3
28
0
Order By: Relevance
“…Previous studies reported several conflicting results on the effect of n -3 PUFAs on NAFLD [ 25 , 26 , 27 , 28 ], without any clear explanation. The conflicting conclusions may be attributed to the genetic polymorphism of FFAR4 among populations, since several FFAR4 mutations exist among populations, as previously reported [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported several conflicting results on the effect of n -3 PUFAs on NAFLD [ 25 , 26 , 27 , 28 ], without any clear explanation. The conflicting conclusions may be attributed to the genetic polymorphism of FFAR4 among populations, since several FFAR4 mutations exist among populations, as previously reported [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effects of dietary n-3 PUFAs in reducing the accumulation of liver lipids have been shown in several experimental animals, including NAFLD and metabolic syndrome [ 28 , 33 , 34 , 35 ]. However, results from clinical studies evaluating the effect of n-3 PUFAs in reducing hepatic fat content in NAFLD are contradictory [ 36 , 37 , 38 , 39 ], and no study has evaluated the effect of dietary n-3 PUFA on hepatic lipid metabolism in cancer animal models provided with chemotherapy treatments. In the present study, we show that hepatic MUFA contained within the TG fraction is significantly reduced while n-3 PUFA content increased in a cancer animal model provided dietary fish oil immediately following the provision of chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our results suggest that the DHA attenuation of BTC-TGFβ-2 -dependent molecular events might not be limited to reversal of fibrosis in NASH ( 25) but also has a promise in preventing NASH's progression into liver cancer. Clinical trials using EPA and/or DHA in NAFLD/NASH therapy have shown mixed, but promising results with significant improvement with disease severity, including hepatosteatosis and liver injury (19)(20)(21)(22)(23)(24). Unfortunately, these studies did not address whether patients that did not respond to therapy represent a cellular/molecular subtype of NAFLD that is not treatable only by ω3 PUFA or perhaps have such severe disease that they are unlikely to respond to any therapeutic agent.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, while there are many studies describing different molecular and cellular effects of ω3 fatty acids (19)(20)(21)(22)(23)(24) and some evidence that they may be an efficient therapy for NAFLD/NASH the key mechanisms of their impact in improving liver health are still unknown.…”
Section: Introductionmentioning
confidence: 99%